P–717 Where do cryopreserved embryos end up after a positive pregnancy test?. (6th August 2021) - Young, E; Argibay, S Garci; Isa, L; Zappacost. Villarroel, M P; Inza, R; Valcarcel, A
Abstract: Study question: What is the destination of supernumerary embryos after a positive pregnancy test? Summary answer: Half of the surplus cryopreserved embryos in assisted reproduction treatments are not transferred. What is known already: Many of the surpernumerary cryopreserved embryos in assisted reproductive technologies are not transferred. This is a constant issue in many fertility centers around the world. Our objective was to report what happens with vitried surplus embryos after IVF in patients with a positive pregnancy test, carrying out an analysis according to age and final evolution of the pregnancy. Study design, size, duration: This is a retrospective descriptive study. We analyzed 245 embryo transfer cycles, performed between January 2013 to December 2017, in 235 patients with a positive pregnancy test and who vitrified surplus embryos. Participants/materials, setting, methods: All the patients underwent treatment with their own oocytes. The variables studied were: age, miscarriage rate (MR) and live birth rate (LBR). We compared the destination of the cryopreserved embryos according to the patient's age and pregnancy evolution. Statistical analysis was performed with Fisher's exact test. Main results and the role of chance: 20% of the IVF cycles (n = 49) were performed in women older than 40 years, 42% between 35 and 39 (n = 103) and 38% in women younger than 35 (n = 94). Average age was 35.8 ± 4.1 years. 859 embryos were cryopreserved (3.5 ± 1.9 cryopreserved embryos/patient). Average search time for surplus embryos was 20.5 ± 17.9 months, rising to 36.9 ± 14.9 months after delivery and decreasing to 8.7 ± 7.8 months after miscarriage (P < 0.0001). Up to date there are 118 (48.2%) patients whose cryopreserved embryos have not been transferred yet. Signficant differences were found in the three groups in using the cryopreserved embryos according to whether or not they had delivery. Almost half of the surplus cryopreserved embryos are not transferred. Regardless of the age of the patient, all groups showed the same behavior regarding the utilization of the cryopreserved embryos after delivery. It is essential to advise couples who perform assisted reproductive technologies, with a good probability of success (regardless of the patient's age), about the responsibility that embryonic cryopreservation entails. Argentine legislation has limitations regarding the availability of cryopreserved surplus embryos. Limitations, reasons for caution: This is a retrospective study. Wider implications of the findings: We believe that Public Health policies related to this issue should be re evaluated based on these results. Trial registration number: Not applicable